Experimental and numerical investigations on undulatory motion of a soft-fin-based underwater robot. (11th July 2022) - Lin, Yu-Chih; Zhang, Dai-Nong
ABSTRACT: An undulatory fin bionic underwater robot that is able to mimic the undulation motions of the median and/or the paired fin of fish is designed and analyzed. A simplified rays-membrane structure system has been developed in order to save computational cost in finite element analysis. The undulatory motion of the soft fins in the water is experimentally measured by using two cameras and the DLTdv system. The dynamic characteristics of the fin structure and the hydrodynamics of the fluid are analyzed by a fluid-structure interaction model developed by the commercial software ANSYS, and the results are compared to those of the experiment for validation. The fin motion of different fin amplitudes (ray swing angles), membrane dimensions and phase difference of adjacent rays are compared to realize the influence of robot design on the motion. It is found in the results that the displacements of the points on the fin membrane obtained by the finite element analysis have the same trend as those by the experiment; hence, the finite element model is verified. It is indicated by the finite element analysis results that the stress of the points on the fin membrane increases with the amplitude. The maximum velocity in one section plane is largest for the 40 mm width fin. The average stress on the fin with 45° phase difference is larger than that of 90° phase difference. Because of the complexity of the soft fin's material behavior and fluid-structure interaction analysis, the finite element analysis model developed in this study has a significant contribution for the soft-fin-based underwater robot design.